Effects of experimental conditions and of addition of natural minerals on syngas production from lignin by oxy-gasification: Comparison of bench- and pilot scale gasification. (15th January 2015) - Pinto, Filomena; André, Rui Neto; Carolino, Carlos; Miranda, Miguel; Abelha, Pedro; Direito, Daniel; Dohrup, Jesper; Sørensen, Hanne Risbjerg; Girio, Francisco
Highlights: Oxygen blown gasification of spent lignin from a second-generation cellulosic ethanol plant. Oxy-gasification of a biomass fraction (lignin) with high tendency for tar formation. Oxy-gasification of a biomass fraction with high contents of silica and alkaline metals. Confirmation of bench-scale oxy-gasification results at pilot-scale. Hot syngas cleaning and upgrading in a two fixed bed catalytic reactors installation. Abstract: Gasification of spent lignin pellets was used to obtain a gas suitable for energy production. Spent lignin was obtained from second-generation cellulosic ethanol demo plant using wheat straw as feedstock. Gasification of lignin did not give rise to any feeding problems, thus no significant changes were needed in the existing gasification installation. The rise of temperature and steam flow rate favoured the formation of H2, while hydrocarbons (C n H m ) and tar contents decreased. The increase of equivalent ratio (ER) also decreased hydrocarbons and tar contents, but syngas higher heating value (HHV) was reduced. The use of natural minerals improved lignin gasification. The presence of dolomite led to the highest H2 and to the lowest C n H m and tar contents. Results obtained at bench-scale were confirmed at pilot-scale, as similar trends were obtained. However, as the residence time in pilot gasifier was higher, greater gas yields with higher H2 and CH4 concentrations were obtained, while tar contents decreased. After syngas hot cleaning and upgrading, the final syngas composition showed to be suitable for a wide range of applications (e.g. energy production and synthesis of chemicals), since it was substantially enriched in hydrogen, whereas tar and heavier gaseous hydrocarbons were completely destroyed.